2007
DOI: 10.1186/1471-2180-7-116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Trichomonas vaginalis surface-associated AP65 and binding domain interacting with trichomonads and host cells

Abstract: Background: AP65 is a prominent adhesin of Trichomonas vaginalis that mediates binding of parasites to host vaginal epithelial cells (VECs). AP65 with no secretion signal sequence, membrane targeting peptide, and anchoring motif was recently found to be secreted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 39 publications
0
52
0
3
Order By: Relevance
“…Although in the literature it is routinely reported that men infected by their partners resolve their infections, there is neither experimental evidence nor clinical studies proving this. Reports have shown the expression of numerous virulence factors that permit this ancient protist to survive in the changing host environment of the female urogenital region (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Iron is an important modulator of upregulation and downregulation of the expression of virulence genes (8,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Although in the literature it is routinely reported that men infected by their partners resolve their infections, there is neither experimental evidence nor clinical studies proving this. Reports have shown the expression of numerous virulence factors that permit this ancient protist to survive in the changing host environment of the female urogenital region (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Iron is an important modulator of upregulation and downregulation of the expression of virulence genes (8,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Several hydrogenosomal enzymes have previously been shown to be expressed on cell surfaces and mediate the cytoadherence of T. vaginalis when its growth medium was supplied with an excessive amount of iron (7,8,10). Although the secondary roles of these hydrogenosomal enzymes remain arguable, biochemical and genetic evidence suggests that a 65-kDa malic enzyme, referred to as AP65 and encoded by the ap65-1 gene, is likely involved in parasitic cytoadherence to human vaginal epithelial cells (11)(12)(13).…”
mentioning
confidence: 99%
“…Preimmune (PI) serum was used as a negative control, and other primary antibodies were used to detect TvTIM and the control proteins in Western blotting (WB), including the following: anti-TvTIMr, an antibody previously generated against the recombinant TvTIM2 protein that recognizes both recombinant TvTIM proteins (23); anti-AP65, an antibody generated against the native AP65 trichomonad adhesin; anti-EhHKr, an antibody generated against the Entamoeba histolytica recombinant hexokinase that cross-reacts with T. vaginalis hexokinase (TvHK); and anti-TvENOr, an antibody generated against the recombinant T. vaginalis alpha-enolase (TvENO; TVAG_329460). The control proteins included the loading control; the adhesin AP65; TvHK, which is upregulated by glucose; and TvENO, which is not affected by glucose (12,29,30). These experiments were performed at least three independent times, with similar results.…”
Section: Methodsmentioning
confidence: 60%